PLASMID PROFILING AND CURING OF TYPHOID (SALMONELLA TYPHI) AND NON-TYPHOID (SALMONELLA ENTERITIDIS) ISOLATES FROM ENUGU, NIGERIA - Ekwem , C. C; Eze, Emmanuel A; Ukwueze , N. M (Global Journal of Chemistry, Biology and Physics (GJCBP), 2024)
Medicine is currently grappling with the issue of antibiotic resistance in bacteria, which has arisen due to the rapid multiplication and widespread dissemination of these organisms, coupled with their ability to effortlessly acquire new genetic material. This work was carried out to profile and cure plasmid of typhoid and non-typhoid Salmonella using thirty-five (35) blood samples taken from students of Godfrey Okoye University. Several analyses such as widal test, morphological analysis, biochemical test, antibiotic sensitivity test, plasmid curing and plasmid profiling were performed. The results showed that among the fifteen isolates obtained that ten were identified as Salmonella typhi and five Samonella enteritidis. Notably, all isolates were resistant to sparfloxacin and cefotaxime, each demonstrating a 90% resistance rate with zones of inhibition less than 13 mm. In contrast, the isolates were susceptible to azithromycin (80%) and levofloxacin (70%), with zones of inhibition exceeding 25 mm. Plasmid curing was performed on eight bacterial isolates that exhibited resistance to more than four antibiotics, followed by a reassessment of their antibiotic sensitivity. Post-curing, these isolates remained highly resistant to sparfloxacin (75%), cefotaxime (62.5%), and augmentin (50%), each with zones of inhibition less than 14 mm. However, resistance to azithromycin and levofloxacin significantly decreased, with only 12.5% of the isolates remaining resistant, and zones of inhibition exceeding 30 mm for these antibiotics. The curing of plasmids resulted in a shift in antibiotic susceptibility for some isolates, where previously resistant isolates became susceptible, while others maintained their resistance. This change underscores the role of plasmids in conferring antibiotic resistance among the bacterial isolates. Molecular analysis revealed that the majority of isolates carried plasmids with high molecular weights ranging from 3kbp to 10kbp, with S2, S3, S5, and S12 losing their 3kbp plasmids and S11, S14, and N8 retaining theirs.